Influence of meteorological phenomena on worldwide aircraft accidents, 1967–2010. (1st December 2017) - Mazon, J.; Rojas, J. I.; Lozano, M.; Pino, D.; Prats, X.; Miglietta, M. M.
ABSTRACT: Based on the information available in databases from relevant national and international organizations from 1967 to 2010, an Aviation Weather Accidents Database (AWAD) was built. According to the AWAD, the weather is the primary cause in a growing percentage of annual aircraft accidents: from about 40% in 1967 to almost 50% in 2010. While the absolute number of fatalities and injured people due to aircraft accidents has decreased significantly, the percentage of fatalities and injured people in accidents attributed to the weather shows a slight increase in the studied period. The influence of turbulence, clear air turbulence, wind shear, low visibility, rain, icing, snow and storms on aircraft accidents was analysed, considering the different phases of flight, the meteorological seasons of the year and the spatial distribution over four zones of the Earth. These zones were defined following meteorological and climatological criteria, instead of using the typical political criteria. A major part of the accidents and accidents attributed to the weather occur in latitudes between 12° and 38° in both hemispheres. It is concluded that actions aimed at reducing the risk associated with low visibility, rain and turbulence, in this order, should have priority to achieve the most significant improvements in air transport safety. Abstract : Worldwide annual number of aircraft accidents and weather‐caused aircraft accidents, 1967–2010, and the percentage of the latter number with respect to the former.